A statistical study of kinetic‐size magnetic holes in turbulent magnetosheath: MMS observations. Issue 8 (29th August 2017) - Huang, S. Y.; Du, J. W.; Sahraoui, F.; Yuan, Z. G.; He, J. S.; Zhao, J. S.; Le Contel, O.; Breuillard, H.; Wang, D. D.; Yu, X. D.; Deng, X. H.; Fu, H. S.; et al.
Abstract: Kinetic‐size magnetic holes (KSMHs) in the turbulent magnetosheath are statistically investigated using high time resolution data from the Magnetospheric Multiscale mission. The KSMHs with short duration (i.e., <0.5 s) have their cross section smaller than the ion gyroradius. Superposed epoch analysis of all events reveals that an increase in the electron density and total temperature significantly increases (resp. decrease) the electron perpendicular (resp. parallel) temperature and an electron vortex inside KSMHs. Electron fluxes at 90° pitch angles with selective energies increase in the KSMHs are trapped inside KSMHs and form the electron vortex due to their collective motion. All these features are consistent with the electron vortex magnetic holes obtained in 2‐D and 3‐D particle‐in‐cell simulations, indicating that the observed KSMHs seem to be best explained as electron vortex magnetic holes. It is furthermore shown that KSMHs are likely to heat and accelerate the electrons. Key Points: Kinetic‐size magnetic holes are statistical investigated by MMS Observed kinetic‐size magnetic holes seem to be best explained as electron vortex magnetic holes Kinetic‐size magnetic holes are likely to heat and accelerate the electrons Plain Language Summary: A nonlinear energy cascade in magnetized turbulent plasmas leads to the formation of different coherent structures which are thought to play an important role in dissipating energy and transporting particles. This study statistically investigate one new type of coherent structure, named electron vortex magnetic hole, used by Magnetospheric Multiscale data. It reveals the common features of this structure, including an increase in the electron density and total temperature, significantly increase (resp. decrease) the electron perpendicular (resp. parallel) temperature and an electron vortex inside these holes. The increase of electron temperature inside the holes indicates that these holes are likely to heat and accelerate the electrons. This gives new clue for energy dissipation in turbulent plasmas.